Sistem Pakar Mendiagnosa Penyakit Tiroid Menggunakan Metode Certainty Factor Berbasis Web - Ariawan, Wayan Eka; I Made Agus Widiana , Putra (Universitas Tabanan, 2023)
Thyroid disease is a swelling or lump in the front of the neck caused by disorders of the thyroid gland. Thyroid disease is a very serious health problem in Indonesia. However, the tendency of long queues, and also the problem of the cost required for the treatment causes people sometimes are reluctant to see a doctor. Besides the limitations of doctors and the uneven number of doctors further worsen the situation. The purpose of this study was to design and build an expert system to diagnose thyroid disease. Expert systems are computer programs that replicate the thought process and expert knowledge in resolving a problem. In conclusion withdrawal, this expert system using the method of Certainty Factor. Where this method the user can provide a value based on the perceived severity of symptoms. Expert system for diagnosing thyroid disease constructed web based with the aim of disseminating information to the public so that the management and prevention efforts early thyroid disease can be done quickly.